1988
DOI: 10.1037/0022-006x.56.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of the WAIS and the WAIS—R: A consideration of level of neuropsychological impairment.

Abstract: Subjects of varying levels of neuropsychological impairment who were administered the revised version of the Wechsler Adult Intelligence Scale (WAIS-R) were found to obtain significantly lower Full Scale, Verbal, and Performance IQs than a comparable group of subjects who were administered the original version (WAIS). Significant main effects for level of impairment were found for all IQ measures irrespective of the Wechsler scale administered. No significant interactions of Scale X Level of Impairment were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The WAIS yielded higher mean IQ scores of 7.6 points for VIQ, 7.1 for PIQ, and 7.7 for FSIQ (Prifitera & Ryan, 1983). In another study (Zarantonello, 1988), comparability of IQ scores from the WAIS and WAIS-R was examined for a group of psychiatric patients referred for neuropsychological evaluation; group mean scores were compared as a function of level of neurological impairment. The two scales were found to yield analogous results at all neurological impairment levels.…”
Section: Comparisons Between the Wais And The Wais-rmentioning
confidence: 99%
“…The WAIS yielded higher mean IQ scores of 7.6 points for VIQ, 7.1 for PIQ, and 7.7 for FSIQ (Prifitera & Ryan, 1983). In another study (Zarantonello, 1988), comparability of IQ scores from the WAIS and WAIS-R was examined for a group of psychiatric patients referred for neuropsychological evaluation; group mean scores were compared as a function of level of neurological impairment. The two scales were found to yield analogous results at all neurological impairment levels.…”
Section: Comparisons Between the Wais And The Wais-rmentioning
confidence: 99%
“…Since 1981, a number of studies have assessed the equivalence of the Wechsler Adult Intelligence Scale (WAIS; Wechsler, 1955) and the Wechsler Adult Intelligence Scale–Revised (WAIS–R; Wechsler, 1981). All of these studies (Edwards & Klein, 1984; Field & Sisley, 1986; Kelly, Montgomery, Felleman, & Webb, 1984; Lippold & Claiborn, 1983; Mishra & Brown, 1983; Mitchell, Grandy, & Lupo, 1986; Prifitera & Ryan, 1983; Quereshi & Ostrowski, 1985; Rabourn, 1983; Rogers & Osborne, 1984; Smith, 1983; Urbina, Golden, & Ariel, 1982; Wechsler, 1981; Zarantonello, 1988) used incidental samples, with subjects ranging in age from 16 to 72 years, and indicated that the WAIS IQs were invariably 3 to 9 points higher than the corresponding WAIS–R IQs.…”
mentioning
confidence: 99%
“…If we use the Full Scale IQ (FSIQ) differences as a basis for classifying the 14 studies involving WAIS and WAIS–R comparisons that were published between 1981 and 1988, they are divisible into three categories: (a) Five studies (Edwards & Klein, 1984; Mishra & Brown, 1983; Mitchell et al, 1986; Quereshi & Ostrowski, 1985; Smith, 1983) reported mean differences of 3 to 5 points; (b) five studies (Field & Sisley, 1986; Kelly et al, 1984; Rabourn, 1983; Urbina et al, 1982; Zarantonello, 1988) reported mean differences of 5 to 7 points; and (c) four studies (Lippold & Claiborn, 1983; Prifitera & Ryan, 1983; Rogers & Osborne, 1984; Wechsler, 1981) reported mean differences of 7 or more points. Studies constituting each category share some characteristics that are different from those shared by studies in other categories.…”
mentioning
confidence: 99%